Sustainable Organisational Identity In State Higher Education Institutions - Shinta Ratnawati; Amin Wibowo; Rr. Tur Nastiti; Sari Sitalaksmi (Jurnal Manajemen, 2024)
This research examines the antecedent, consequence, and moderating factors for sustainable organisational identity. Specifically, based on the Resource View Theory, this research aims to examine the effects of anthropomorphism and agile leadership on sustainable organisational identity, the effect of sustainable organisational identity on competitive advantage, and the moderating effect of planned organisational change between sustainable organisational identity and competitive advantage. The sample was 74 state universities in Indonesia. Variable measurement uses questionaries. Data analysis uses path analysis. Based on data analysis, anthropomorphism positively affects sustainable organisational identity in state higher education institutions. Second, agile leadership positively affects sustainable organisational identity in state higher education. Third, sustainable organisational identity positively affects competitive advantage in state higher education institutions. Fourth, planned organisational change strengthens the positive effect of sustainable organisational identity on competitive advantage in state higher education.